Решить а) (х-1) (х-3)=0 б) (х+4) (3+х)=0

Rukgz Rukgz    3   18.08.2019 04:20    0

Ответы
1231234564561 1231234564561  05.10.2020 02:12
А) (х-1)(х-3)=0
х-1=0 или х-3=0
х=1 или х=3
ответ: 1;3

б) (х+4)(3+х)=0
х+4=0 или 3+х=0
х=-4 или х=-3
ответ: -4;-3
ПОКАЗАТЬ ОТВЕТЫ
aibarealmadrid aibarealmadrid  05.10.2020 02:12
А) (х-1)(х-3)=0
х^2-3х-х+3=0
х^2-4х+3=0
х1+х2=4
х1× х2=3
х1=3 х2=1

б) (х+4)(3+х)=0
3х+х^2+12+4х=0
х^2+7х+12=0
х1+х2=-7
х1× х2=12
х1=-4 х2=-3
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра